Research of Light Use Efficiency for Paddy Rice Using Multi-Angle Hyperspectral Observations - Guo, Jianmao; Zhang, Zhanhao; Guo, Caiyun; Jin, Shuyuan (Frontiers in Earth Science, 2022)
Light Use Efficiency (LUE) is a critical variable for modeling Gross Primary Production (GPP) of vegetation. Estimating LUE over space and time accurately is a key of monitoring crop growth. The Photochemical Reflectance Index (PRI) is based on reflectance at 531 and 570 nm, which reflects the xanthophyll cycle process of plants under different radiation conditions and has great potential in predicting Light Use Efficiency (LUE). But PRI may be affected by changes in observation angle and solar position during canopy observation. In this study, we used tower based multi-angle spectral reflectance observations and corresponding eddy covariance (EC) of a rice paddy field stand in ShouXian station which is located at middle and lower reaches of the Yangtze River in China to calculate PRI and LUE respectively, and explored the ability of PRI under different observation angles to track LUE in rice fields. Then, we used semi-empirical kernel driven bidirectional reflectance distribution function (BRDF) model to interpret these PRI which were subject to directional reflectance effects and to improve the accuracy of PRI estimating Lue. The results indicate that there was a stronger relationship between PRI and LUE on rice canopy in sunny day but a poor relationship in cloudy day when keeping the observed azimuth angle (OZA) at 0°, where R2 = 0.4 and R2 = 0.26 respectively. After distinguishing different zenith angles scattering areas, the relationship between PRI-LUE was improved, where R2=0.7 in the backscatter direction with an OZA of 60°, which was greatest. Using the semi-empirical kernel driven BRDF model to correct the mixed multi-angle PRI also improved the relationship of PRI-LUE (R2=0.72). This study highlighted an improvement of correlation between LUE and PRI by multi-angle observation at rice growth period. We also found that photosynthetically active radiation (PAR), vapor pressure deficit (VPD) and temperature (Ta) had some influence on the LUE, PRI and their relationship. Our research suggests that PRI can track the LUE of the rice growth period well when considering environmental factors and vegetation canopy structures.